2019
DOI: 10.1016/j.ymgmr.2019.100474
|View full text |Cite
|
Sign up to set email alerts
|

Drug screening for Pelizaeus-Merzbacher disease by quantifying the total levels and membrane localization of PLP1

Abstract: Background Pelizaeus-Merzbacher disease (PMD) is caused by point mutations or copy number changes in the proteolipid protein 1 gene ( PLP1 ). PLP1 is exclusively localized in the myelin sheath of oligodendrocytes. Amino acid-substituted PLP1 protein is unable to fold properly and is subsequently degraded and/or restrictedly translated, resulting in a decrease in the PLP1 protein level and a failure to localize to the membrane. Furthermore, misf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Previous studies revealed that overexpression of PLP1 enhanced the accumulation of lipids in the myelin sheath, thereby promoting the progression of diseases in the central nervous system, such as Pelizaeus-Merzbacher disease [ 32 , 33 ]. Furthermore, PLP1 has the potential to inhibit the endoplasmic reticulum [ 34 ]. Given the evidence that the endoplasmic reticulum is a key process that can induce cell apoptosis in GBM [ 35 ], we consider that PLP1 is involved in the progression of elderly patients with GBM by inhibiting the processes of the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that overexpression of PLP1 enhanced the accumulation of lipids in the myelin sheath, thereby promoting the progression of diseases in the central nervous system, such as Pelizaeus-Merzbacher disease [ 32 , 33 ]. Furthermore, PLP1 has the potential to inhibit the endoplasmic reticulum [ 34 ]. Given the evidence that the endoplasmic reticulum is a key process that can induce cell apoptosis in GBM [ 35 ], we consider that PLP1 is involved in the progression of elderly patients with GBM by inhibiting the processes of the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
“…Pelizaeus-Merzbacher disease (PMD) is a pathology linked to the X chromosome that causes the demyelination of the CNS due to a mutation in the gene that codes for the myelin protein PLP. The severity of this pathology depends on both the severity of the mutation and the ability of PLP to escape from the ER [45]. There are also PMD-like forms, in which mutations of genes that code for other myelin proteins, such as MAG.…”
Section: Mitochondria and Endoplasmic Reticulum In Oligodendrocytesmentioning
confidence: 99%
“…Pelizaeus-Merzbacher disease (PMD) is a pathology linked to the X cromosoma that causes dysmyelination of the CNS due to a mutation in the gene that codes for the myelin protein PMD. The severity of this pathology depends on both the severity of the mutation and the ability of PLP to escape from the ER [42]. There are also PMD-like forms in which mutations of genes that code for other myelin proteins, such as MAG.…”
Section: Mitochondria and Endoplasmic Reticulum In Oligodendrocytesmentioning
confidence: 99%